Enhancing agriculture products traceability towards sustainability - Cordeiro, M.; Basto-Fernandes, V.; Silveirinha, J.; Ferreira, J. (Hybrid intelligent systems: 23rd International Conference on Hybrid Intelligent Systems (HIS 2023), Conference proceedings, 2025)
The agricultural industry is undergoing a transformative shift boosted by the Farm to Fork (F2F) strategy, a crucial part of the European Green Deal that directly involves food production. The aim of F2F is to push European agriculture to move from compliance to performance, which will impel farmers to decrease the application of pesticides and fertilizers, improve nutrient management, and reduce emissions, towards a focus shift of greater transparency and traceability in the supply chain. And blockchain technology has emerged as a powerful tool to facilitate this change. The Portuguese Tomato industry plays a significant role in international trade where is ranked in seventh position in the TOP10 for foreign sales of tomato products. This paper explores the application of blockchain technology in enhancing traceability within the tomato industry supply chain, as traceability is crucial to improve food safety and meet the requirements of relevant protocols, industrial quality control, and consumer confidence. However, traditional paper-based systems and databases have limitations in ensuring real-time, tamper-proof traceability. Blockchain offers a decentralized, immutable ledger that securely records each step in the tomato production, processing procedures and distribution process. In this paper, we examine the key challenges in tomato traceability and how blockchain addresses these challenges. We discuss the principles of blockchain technology, emphasizing its transparency, security, and decentralization. Moreover, we present case studies and real-world implementations of blockchain in tomato traceability, showcasing the tangible benefits of this technology. Blockchain’s role in tomato traceability extends beyond food safety; it empowers the industry and consumers to make informed choices about the products they consume, promotes fair trade, and supports sustainable agriculture. We also discuss the challenges and considerations in adopting blockchain for tomato traceability, including data privacy, interoperability, and scalability. As a conclusion, this paper highlights the potential of blockchain technology to revolutionize tomato industry traceability by ensuring transparency and security throughout the supply chain. It emphasizes the importance of this innovation in ensuring food safety, promoting sustainability, and meeting the increasing demands of conscious consumers. Blockchain’s impact on tomato traceability is poised to create a more efficient, trustworthy, and sustainable tomato supply chain for the future.